2016
DOI: 10.1371/journal.pone.0159885
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Sensors of Organic Advocacy: The Case of Leonardo DiCaprio and Climate Change

Abstract: The strategies that experts have used to share information about social causes have historically been top-down, meaning the most influential messages are believed to come from planned events and campaigns. However, more people are independently engaging with social causes today than ever before, in part because online platforms allow them to instantaneously seek, create, and share information. In some cases this “organic advocacy” may rival or even eclipse top-down strategies. Big data analytics make it possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 37 publications
0
36
0
2
Order By: Relevance
“…[4042] Twitter has been used to investigate interest toward a wide range of diseases, such as cancer or infectious diseases, among others. It has been exploited to quantitatively assess the effect of advocacy as well [42] or the impact of scientific conferences. [43]…”
Section: Methodsmentioning
confidence: 99%
“…[4042] Twitter has been used to investigate interest toward a wide range of diseases, such as cancer or infectious diseases, among others. It has been exploited to quantitatively assess the effect of advocacy as well [42] or the impact of scientific conferences. [43]…”
Section: Methodsmentioning
confidence: 99%
“…As it can be seen at the graph, there was an increase of 25% (44-55 RSV) in the relative searches value within the five-year period relating to 'climate change' after DiCaprio's speech at the Academy Awards event. A more detailed study by Leas et al [35] has found that one hour after DiCaprio spoke, searches increased by 261%, the day after the speech the values stayed at 78%, and steadily crawled down to 39% in the next 4 days. When compared to the COP and Earth Day, the study identifies that the searches volume at the day of his acceptance speech were 3.8 and 4.3 times higher than the daily average during those previous events, respectively [35].…”
Section: Public Figures-leonardo Dicaprio Speech At the Academy Awardmentioning
confidence: 97%
“…While he has spoken on environment issues in the past, this was an event with global coverage garnering a broader reach. Recent research 7 looks at the impact of DiCaprio's acceptance speech on the media coverage, tweets and Google searches of 'climate change' or 'global warming' . While traditional media studied showed little change, there were over 250,000 related tweets that day -a 636% increase on expectations.…”
Section: Editorialmentioning
confidence: 99%